The Active Learning Strategies : To Reduce Speaking Anxiety In Maharah Kalam Classes At Mts Mambaus Sholihin - Muhammad A'inul Haq (LUGHATI: Jurnal Pendidikan Bahasa Arab, 2026)
Speaking anxiety remains a major psychological barrier in the development of Arabic speaking skills (maharah al-kalam), particularly among students in Islamic boarding school-based madrasahs. This study examined the effectiveness of active learning strategies in reducing speaking anxiety and improving the Arabic speaking performance of eighth-grade students at MTs Mambaus Sholihin. A quantitative approach was employed using a one-group pretest–posttest pre-experimental design. The participants consisted of 30 students selected purposively based on their relatively high levels of speaking anxiety and low classroom participation. Data were collected using the 33-item Foreign Language Classroom Anxiety Scale (FLCAS) and an Arabic speaking performance rubric covering fluency, pronunciation, vocabulary, and grammar. The intervention was conducted over six weeks through three active learning strategies: Inside–Outside Circle, role-play, and Think–Pair–Share. The data were analyzed using descriptive statistics and a paired-samples t-test. The findings revealed that the students’ mean speaking anxiety score decreased from 118.45 in the pretest to 82.30 in the posttest, representing a mean reduction of 36.15 points. The difference was statistically significant, t(29) = 23.51, p < .001. Furthermore, the students’ mean speaking performance score increased descriptively from 64.20 to 78.50. These findings indicate that active learning strategies can create a more supportive, collaborative, and low-pressure learning environment, thereby reducing fear of negative evaluation and encouraging students to participate more confidently in Arabic communication. However, because the study did not employ a control group and did not conduct a separate inferential analysis of speaking performance, the results should be interpreted cautiously. Further research involving larger samples, control groups, and comprehensive statistical analyses is recommended..